Zasada racjonalności w zjawisku administracji publicznej w kontekście tzw. prywatyzacji zadań publicznych - Pakuła, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Public administration is also a social phenomenon. Performing of public tasks is a social activity. They may take the form of purposefully rational and valuably rational activities. Entrusting public tasks to non-public entities should be primarily seen as a valuably rational activity. Fundamental value is the public interest
Keywords: public administration; social activity; rationality; value; public interest